British Military Experience of Pre-Hospital Paediatric Trauma in Afghanistan. Issue 3 (1st September 2010) - Walker, N; Russell, RJ; Hodgetts, TJ
Abstract : Introduction: Trauma is a leading cause of death in children. Life support courses have been developed to reduce the mortality and morbidity of children suffering trauma; differences in anatomy and physiology may produce different injury patterns to adults when children are exposed to trauma, challenging the care providers. Methods: A retrospective analysis of all paediatric patients transported by the helicopter-borne MERT between 01 May 2006 and 31 December 2007 in Helmand Province, Afghanistan. Results: 78 children were brought in over the study period by the MERT team representing 7.3% of MERT casualties and 2.2% of the total seen in the Emergency Department. Breakdown by demographics, triage category, mechanism of injury, and treatment is given. Conclusion: A significant number of paediatric patients are treated by the deployed pre-hospital team. All military pre-hospital care providers should gain training and experience in the care of the seriously injured child prior to deployment.